Scored patient-generated subjective global assessment, albumin and transferrin for nutritional assessment of gastrostomy fed head or neck cancer patients - Marta Alexandra Correira Pereira; Carla Adriana Santos; José Almeida Brito; Jorge Fonseca (Nutrición Hospitalaria, 2014)
Introduction: Gastrostomy fed head or neck cancer patients frequently have impaired speech capacities. Enteral feeding teams frequently depend on laboratorial or anthropometrical parameters for nutritional assessment. Aims: In these patients, this study aimed to evaluate: (1) the practicability of Scored - Patient-Generated Subjective Global Assessment (PG-SGA); (2) their nutritional status using the Scored-PG-SGA; (3) association of serum albumin and transferrin values to the nutritional status rating using PG-SGA. Methods: On adult outpatients with head or neck cancer under prolonged (> 1 month) gastrostomy feeding, Scored-PG-SGA, albumin and transferrin were evaluated during the same appointment. Results: Scored-PG-SGA was easily feasible in 42 patients, even in patients with speech difficulties. Twenty-five patients were moderately/severely undernourished (PG-SGA/B+C). Scored-PG-SGA rated 41 patients as ≥ 2, thus needing nutritional/pharmacologic intervention. Albumin was low in 13 patients. Transferrin was low in 19 patients. Average albumin and transferrin in moderately/severely undernourished patients (PG-SGA/B+C) was significantly lower than in well-nourished (PG-SGA/A). There was association between Scored-PG-SGA rating, albumin and transferrin. Conclusions: In PEG fed head or neck cancer patients, PG-SGA was practicable and useful, even in patients with impaired speaking skills. Most patients displayed moderate/severe malnutrition (PG-SGA/B+C). Scored-PG-SGA rated 41 patients as needing for nutritional/pharmacological intervention. Scored-PG-SGA should be systematically included in the evaluation of these patients. In these patients, albumin and transferrin levels showed relation with Scored-PG-SGA and should be considered as nutritional biomarkers.